Приобретение права собственности на бесхозяйные вещи - Shebetnikova, Yekaterina (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
The study aims at an evaluation of the acquisition of the ownership of the unclaimed property. The author present this form of the acquisition of the right to property in the Russian Civil Code emphasising the necessity of fulfilling law norms.